Association between hypertension and stroke among Young Thai adults in Bangkok, Thailand - Ratanaporn Bandasak (2018)
A hospital based case-control study was conducted to assess the association between hypertension and stroke among young Thai adults at a private hospital in Bangkok, Thailand. The study population was comprised of 98 inpatients with a first diagnosis of stroke and 98 inpatients without stroke admitted from 2006 to 2008, aged 18-45 years. Cases were matched with controls by sex and five year age group intervals. Risk factors for stroke, including hypertension were collected using a questionnaire. Significant finding on physical examination and blood testing were obtained from the patients' charts. Multivariate analysis revealed significant risk factors for stroke were: diagnosis of hypertension (adjusted OR 8.94; 95% CI 1.47-54.34), family history of stroke (adjusted OR 16.15; 95% CI 1.71-151.82), history of no or irregular exercise (adjusted OR 8.06; 95% CI 1.12-57.60) and having a low high density lipoprotein level (adjusted OR 5.93; 95% CI 1.11-31.52). Hypertension was the greatest risk factor for stroke among young Thai adults. Modification of lifestyle to reduce risk for stroke should focus on exercise, regular health check-ups and adequate treatment of hypertension.